Personalising learning through the use of technology - Robinson, C; Sebba, J (2010)
In March 2005, the Department for Education and Skills published its e-strategy, Harnessing Technology (DfES, 2005, Harnessing technology: Transforming Learning and Children's Services). Within this, two of its key objectives were: firstly to transform teaching and learning, and help to improve outcomes for children and young people, through shared ideas, more exciting lessons, and online help for professionals. Secondly, to engage 'hard to reach' learners, with special needs support, in more motivating ways of learning, and give them more choice about how and when they learn. This paper reports findings from a research project, funded by Becta, which formed part of Becta's broader role in shaping and delivering the government's Harnessing Technology e-strategy. The project ran for 7 months, from September 2007 to March 2008. It aimed to find out how learners and their representatives have influenced schools' decisions to introduce, support and grow opportunities for personalising learning through the use of technology. The paper focuses specifically on the key facilitators and barriers, from both staff and learners' perspectives, which influence the level of personalised learning activities using digital technology in schools. © 2009 Elsevier Ltd. All rights reserved.